Rural housing and sustainable regional development - The national rural housing program in Nova Olinda/Ce - Costa, Mila Fonteles Barbosa Ferreira; Da Costa, Celme Torres Ferreira; Da Rocha Grangeiro, Rebeca; Da Silva Alencar, Girlaine Souza [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2019)
Housing is one of the themes related to social inclusion and has been recurring in the last decade for the projection of the Minha Casa Minha Vida Program (PMCMV). The access to the own house presents to the Brazilian the possibility of the transformation of its space reality. The National Rural Housing Program (PNHR), part of the PMCMV, promotes access to housing through the production of new units or the renovation of existing units. The object of study of this research is the PNHR, applied in Nova Olinda-CE and has as general objective to identify the characteristics that classify the PNHR as an agent of the rural regional development and its sustainable bias for the economic, environmental and social management of its beneficiaries. For the investigation, interviews were conducted, and the respondents were the managers of the Union of Family Farm Workers (SINTRAF) and Caixa Econômica Federal (CEF). After analyzing the interviews, the research presented a sustainable profile of the PNHR, through the interviewees' indications about care in the transition of the families, maintenance of the activities developed and permanence in the rural area with better living conditions and without cost burden on life.
Habilitação Rural e Desenvolvimento Regional Sustentável: O Programa Nacional de Habitação Rural em Nova Olinda/CE
Keywords: Government Program; Low Income; Minha Casa Minha Vida Program